Polish Encounter with a Minimum Taxation: Revenue Tax on Commercial Buildings - Jamroży, Marcin; Łożykowski, Aleksander (Journal of Finance and Financial Law, 2021)
The purpose of the article/hypothesis. The purpose of the article is to present the concept of the minimum tax on revenues from commercial buildings and to evaluate the regulation introduced, including the formulation of de lege ferenda postulates. Methodology. The regulatory evolution of the tax structure in 2018–2020 was analyzed and its impact on taxpayers’ settlements. Results of the research. The hypothesis that the minimum tax in the form of a tax on revenues from commercial buildings is a non-excessive anti-abusive measure is verified. One of the purposes of this tax is, in particular, to prevent tax avoidance and profit shifting by large real estate companies owning commercial real estate of significant value. Only about 1/3 of taxpayers did not fully deduct the minimum tax due on commercial buildings from the corporate income tax calculated on general basis. The effect of the increased tax burden, at least temporarily, is mitigated by a number of solutions securing the neutrality of this tax and a relatively low level of the minimum tax.